Weekly platinum-based chemotherapy versus 3-weekly platinum-based chemotherapy for newly diagnosed ovarian cancer (ICON8): quality-of-life results of a phase 3, randomised, controlled trial. Issue 7 (July 2020) - Blagden, Sarah P; Cook, Adrian D; Poole, Christopher; Howells, Lesley; McNeish, Ian A; Dean, Andrew; Kim, Jae-Weon; O'Donnell, Dearbhaile M; Hook, Jane; James, Elizabeth C; White, Ian R; Perren, Timothy; et al.
Summary: Background: The ICON8 study reported no significant improvement in progression-free survival (a primary endpoint) with weekly chemotherapy compared with standard 3-weekly treatment among patients with epithelial ovarian cancer. All ICON8 patients were eligible to take part in the accompanying health-related quality-of-life study, which measured the effect of treatment on self-reported wellbeing, reported here. Methods: In this open-label, randomised, controlled, phase 3, three-arm, Gynecologic Cancer Intergroup (GCIG) trial done at 117 hospital sites in the UK, Australia, New Zealand, Mexico, South Korea, and Republic of Ireland, women (aged at least 18 years) with newly diagnosed, histologically confirmed International Federation of Gynecology and Obstetrics stage IC–IV ovarian cancer and an Eastern Cooperative Oncology Group performance status of 0–2 were randomly assigned (1:1:1) centrally using minimisation to group 1 (intravenous carboplatin area under the curve [AUC]5 or AUC6 and 175 mg/m 2 intravenous paclitaxel every 3 weeks), group 2 (carboplatin AUC5 or AUC6 every 3 weeks and 80 mg/m 2 paclitaxel weekly), or group 3 (carboplatin AUC2 weekly and 80 mg/m 2 paclitaxel weekly). Randomisation was stratified by GCIG group, disease stage, and outcome and timing of surgery. Patients and clinicians were not masked to treatment assignment. Patients underwent immediate or delayed primary surgery according to clinicians' choice. Patients were asked to complete European Organisation for Research and Treatment of Cancer QLQ-C30 and QLQ-OV28 questionnaires at enrolment, before each chemotherapy cycle, then 6-weekly up to 9 months, 3-monthly up to 2 years, and 6-monthly up to 5 years. Quality of life was a prespecified secondary outcome of the ICON8 study. Within the quality-of-life study, the co-primary endpoints were QLQ-C30 global health score at 9 months (cross-sectional analysis) and mean QLQ-C30 global health score from randomisation to 9 months (longitudinal analysis). Data analyses were done on an intention-to-treat basis. The trial is registered on ClinicalTrials.gov, NCT01654146 and ISRCTN Registry, ISRCTN10356387, and is currently in long-term follow up. Findings: Between June 6, 2011, and Nov 28, 2014, 1566 patients were recruited into ICON8 (522 were included in group 1, 523 in group 2, and 521 in group 3). Baseline quality-of-life questionnaires were completed by 1438 (92%) of 1566 patients and 9-month questionnaires by 882 (69%) of 1280 patients. We observed no significant difference in global health score at 9 months (cross-sectional analysis) between study groups (group 2 vs group 1, difference in mean score 2·3, 95% CI −0·4 to 4·9, p=0·095; group 3 vs group 1, −0·8, −3·8 to 2·2, p=0·61). Using longitudinal analysis, we found lower global health scores for those receiving weekly paclitaxel than for those receiving 3-weekly chemotherapy (group 2 vs group 1, mean difference −1·8, 95% CI −3·6 to −0·1, p=0·043; group 3 vs group 1, −2·9, −4·7 to −1·1, p=0·0018). Interpretation: We found no evidence of a difference in global quality of life between treatment groups at 9 months; however, patients receiving weekly treatment reported lower mean quality of life across the 9-month period after randomisation. Taken together with the lack of progression-free survival benefit, these findings do not support routine use of weekly paclitaxel-containing regimens in the management of newly diagnosed ovarian cancer. Funding: Cancer Research UK, Medical Research Council, Health Research Board Ireland, Irish Cancer Society, and Cancer Australia.